Student Satisfaction Information System on Administrative Services in Information Engineering Study Program Muhammadiyah University Bengkulu - Ujang Juhardi; Diana Diana; Marhalim Marhalim; Gunawan Saputra (Penerbit Jurnal Indonesia, 2022)
The level of student satisfaction with the services of the Administrative Services section of the Faculty of Engineering, University of Muhammadiyah Bengkulu is not yet known. To determine the level of student satisfaction in receiving these services, it is necessary to create a system that can measure the level of student satisfaction with the services provided. In conducting this research, the development method of the System Development Life Cycle (SDLC) is a gradual approach to analyze and build a system design using a specific cycle for user activities and the approach method used in measuring the level of satisfaction using a licker scale. This system is built with the XAMPP tool that can test applications without requiring an internet connection, PHP programming language and MySQL database. The results of the system made can help and make it easier to find out the level of student satisfaction with the services provided and the faculty in particular can quickly improve and improve the performance of services that get bad ratings. From the overall assessment, the value of service satisfaction level is 89.26 with a very good predicate. It is hoped that this application is always up to date so that it follows the development of Android-based technology.